PROUD: Effects of preoperative long-term immunonutrition in patients listed for liver transplantation - Nickkholgh, Arash (BioMed Central, 2007)
BACKGROUND: Patients with end stage liver disease are characteristically malnourished which is associated with poor outcome. Formulas enriched with arginine, ω-3 fatty acids, and nucleotides, "immunonutrients", potentially improve their nutritional status. This study is designed to evaluate the clinical outcome of long-term "immunonutrition" of patients with end-stage liver disease while on the waiting list for liver transplantation. METHODS/DESIGN: A randomized controlled double blind multi-center clinical trial with two parallel groups comprising a total of 142 newly registered patients for primary liver transplantation has been designed to assess the safety and efficacy of the long-term administration of ORAL IMPACT(®), an "immunonutrient" formula, while waiting for a graft. Patients will be enrolled the day of registration on the waiting list for liver transplantation. Study ends on the day of transplantation. Primary endpoints include improved patients' nutritional and physiological status, as measured by mid-arm muscle area, triceps skin fold thickness, grip strength, and fatigue score, as well as patients' health related quality of life. Furthermore, patients will be followed for 12 postoperative weeks to evaluate anabolic recovery after transplantation as shown by reduced post-transplant mechanical ventilation, hospital stay, wound healing, infectious morbidities (pneumonia, intraabdominal abscess, sepsis, line sepsis, wound infection, and urinary tract infection), acute and chronic rejection, and mortality. DISCUSSION: Formulas enriched with arginine, ω-3 fatty acids, and nucleotides have been proven to be beneficial in reducing postoperative infectious complications and length of hospital stay among the patients undergoing elective gastrointestinal surgery. Possible mechanisms include downregulation of the inflammatory responses to surgery and immune modulation rather than a sole nutritional effect. TRIAL REGISTRATION: ClinicalTrials.gov NCT00495859